Multiple-Unit Holdings Yield Attenuated Endowment Effects - Burson, Katherine; Faro, David; Rottenstreich, Yuval (Management Science, 2013)
Previous endowment effect experiments have examined circumstances in which people encounter a single unit of a good (e.g., one chocolate). We contrast single-unit treatments with multiple-unit treatments in which participants encounter several units of a good (e.g., five chocolates). We observe endowment effects of typical magnitude for singleton holdings but attenuated endowment effects for multiple-unit holdings. Moreover, endowment effects consistently arise for singletons even as the definition of a unit is altered. For instance, participants holding one piece of chocolate show an endowment effect of standard size, but so do participants holding one box of chocolates. Yet the box contains about 20 individual pieces of chocolate, and participants given that many separate pieces show a substantially attenuated endowment effect. We thus propose the property of “unit dependence”: the definition of a unit can change, but contingent on any given definition, a pronounced endowment effect may emerge for singletons but not multiples. This paper was accepted by Teck Ho, decision analysis.